Factors influencing career choice amongst fresh graduate students in a Public University - Tan Pei, Yin (Universiti Malaysia Sarawak, 2019)
The objective of this study is to investigate the factors that influence career choice amongst fresh graduate students in a public university. The factors investigated are parental factor, personal interest and career opportunity. A sample size of 100 HRD fresh graduate students were chosen in this study. Questionnaire is used as research instrument in this study. The reliability of the variables in the questionnaire using Cronbach alpha is 0.910. In this study, descriptive (frequency and percentage) and inferential statistics (Pearson Correlation Coefficient Analysis, Independent-sample t-Test and Multiple Regression Analysis) are used to analyse data. Finding oft-test shown that there is no association between gender and career choice. Pearson Correlation analysis reveals that there is a moderate positive correlation between parental factor and career choice. However, there has a high positive correlation between personal interest and career choice and between career opportunity and career choice. Multiple Regression Analysis shown that career opportunity is the most dominant factor that influences career choice. Hence, it is concluded that employers can apply this finding to attract and retain more talented employees.